Social media objectives and challenges of law libraries: A systematic literature review - Intahchomphoo, Channarong; Jeske, Margo; Landriault, Emily (Université d'Ottawa | University of Ottawa, 2016)
The purpose of this paper is to examine the scholarly peer-reviewed publications relating to social media objectives and challenges of law libraries. The methodology is that of a systematic literature review. The studies included in this systematic literature review show that the social media objectives of law libraries are: promoting and marketing resources and services, supporting legal research teaching and tutorials, and providing reference services. Secondly, law libraries face some challenges with their social media usage regarding the quality and scope of content, technological difficulties, and online privacy.
Keywords: Social media; law libraries; systematic literature review